Intent-driven end-to-end network slicing orchestration and control - Xiaoxue ZHAO; Fuguo XUE; Lulu ZHANG; Ying OUYANG; Chungang YANG (Dianxin kexue)
The 6G system will realize diversified and customized on-demand network services for thousands of industries.End-to-end network slicing can provide users with on-demand and flexible service guarantees.However, the existing network service orchestration and control based on network slicing has problems such as high manual participation, high configuration complexity, and high operation and maintenance cost.Therefore, a solution is urgently needed to meet these challenges.Intent-driven network has the characteristics of flexible reconfiguration and adaptive policy optimization, which can improve the user’s end-to-end service experience.An intent-driven end-to-end network slicing orchestration and control system architecture was proposed, which consisted of business application layer, intent-enabled layer and infrastructure layer.On this basis, the intent parsing module, orchestration and control module were designed.Furthermore, a utility evaluation model was constructed from the perspectives of user satisfaction and system intelligence, and system utility was evaluated through simulation.